Pengaruh Beauty Vlogger Review, Self Congruity Terhadap Purchase Decision Dan Repurchase Intention Pada Pengguna Scralett Whithening Di Kabupaten Pasuruan - Rivita Nadiatul Islamiyah; Nur Ajizah (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
The purpose of this study was to determine the effect of Beauty Vlogger Review, Self Congruity on Purchase Decision and Repurchase Intention. This research was conducted on Scarlett Whitening Users. This type of research is associative research using a quantitative approach. The data collection technique used was a questionnaire. The selection of this research sample uses Purpose Sampling. The method of analysis and data processing is carried out using the path analysis method. Based on the results of this study, it can be seen that the Beauty Vlogger Review has a positive and significant effect on Purchase Decision, Self Congruity has a positive and significant effect on Purchase Decision, Beauty Vlogger Review has a positive and insignificant effect on Repurchase Intention, Self Congruity has a positive and significant effect on Repurchase Intention , and Purchase Decision has a positive and significant impact on Repurchase Intention.